Climate change and health risks: Perceptions of risk types, vulnerable groups, and the role of health workers at primary health centers - Muchsin, Gaisha HA.; Khalisa, Ighra; Satria, Darma; Giannakos, Antonios; Kurniawan, Hendra; Pratama, Rovy (Trends in Infection and Global Health, 2025)
Global climate change poses significant health risks by altering environmental conditions, weather patterns and disease dynamics that directly affect human health. Health workers serve as critical agents in recognizing, managing, and mitigating health risks associated with climate change. Their perception and awareness are therefore pivotal in shaping effective health responses. The aim of this study was to determine health workers' perceptions of climate change as a threat to human health. The study was conducted in 11 primary healthcare centers (Pusat Kesehatan Masyarakat, Puskesmas) in Banda Aceh and involved 84 health workers. Data were collected using a questionnaire instrument that had been tested for validity (mean content validity ratio, CVR, and content validity index, CVI=0.83) and reliability (Cronbach's Alpha=0.865). Data were analyzed using index value calculations. The results indicate that most health workers had moderate perceptions of climate change (82%) and its associated health risks (85%). However, only 44% demonstrated moderate awareness regarding vulnerable community groups, and 58% showed moderate awareness regarding the role of health workers in mitigating climate-related health impacts. This study is expected to provide theoretical insights for understanding and evaluating health workers' perceptions of climate-related health risks. Practically, the findings may support government efforts in evaluating and formulating health service strategies, improving the perception of health workers to face the health risks of climate change, and providing education to the public.